Está en la página 1de 2

FORMULAS TRIGONOMETRICAS

IDENTIDADES FUNDAMENTALES
sen 2 x + cos 2 x = 1

sen 2 x = 1 cos 2 x

tg 2 x + 1 = sec 2 x

tg 2 x = sec 2 x 1

cos 2 x = 1 sen 2 x
cot 2 x + 1 = cosec 2 x

RAZONES INVERSAS
1
sec x = -------cos x

1
cosec x = ------sen x

sen x
tg x = ---------cos x

1
tag x = ---------cotg x
cos x
cotg x = --------sen x

ANGULO SUMA
sen ( x + y ) = sen x . cos y + sen y . cos x

cos ( x + y ) = cos x . cos y sen x . sen y

tg x + tg y
tg ( x + y ) = ---------------1 tg x . tg y

cotg x . cotg y - 1
cot ( x + y ) = ----------------------cotg x + cotg y
ANGULO DIFERENCIA

sen ( x y ) = sen x . cos y sen y . cos x

cos ( x y ) = cos x . cos y + sen x . sen y

tg x tg y
tg ( x y ) = ---------------1 + tg x . tg y

cotg x . cotg y + 1
cotg ( x y ) = ------------------------cotg x cotg y
ANGULO DUPLO

sen 2x = 2 sen x cos x


2

cos 2x = 2 cos x 1

cos 2x = cos 2 x sen 2 x

cos 2x = 1 2 sen 2 x

2 tg x
tg 2x = ------------1 tg 2 x

1 cotg 2 x
cotg 2x = ---------------2 cotg x

ANGULO MITAD Y ANGULO NEGATIVO


___________
_________
1 cos x
sen ( x/2 ) =
1 cos x
cos ( x/2 ) = 1 + cos x
tg ( x/2 ) = ----------------
2

2
1 + cos x
.

sen ( - x ) = - sen x

cos ( - x ) = cos x

tg (- x ) = - tg x

SUMA EN PRODUCTO
x+y
xy
sen x + sen y = 2 sen ( ------- ) cos ( ------- )
2
2

xy
x+y
sen x sen y = 2 sen ( ------- ) cos ( ------- )
2
2

x+y
xy
cos x + cos y = 2 cos ( ------- ) cos ( ------- )
2
2

x+y
x-y
cos x cos y = - 2 sen ( ------- ) sen ( ------- )
2
2

PRODUCTO EN SUMA
sen ( x + y ) + sen ( x y )
sen x . cos y = ---------------------------------2

cos ( x + y ) + cos ( x y )
cos x . cos y = ---------------------------------2

cos ( x y ) cos ( x + y )
sen x . sen y = --------------------------------2
LEY DEL SENO
A
c

a
b
c
---------- = --------- = --------sen A
sen B
sen C

C
a
LEY DEL COSENO
a 2 = b 2 + c 2 2 b c cos A

b 2 = a 2 + c 2 2 a c cos B
c

b
c 2 = a 2 + b 2 2 a b cos c

C
a